Морфофункціональні зміни в ушкоджених тканинах ока тварин та активність репаративних процесів за впливу стовбурових клітин - Шупик, Олександр Васильович (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня кандидата ветеринарних наук зі спеціальності 16.00.02 «Патологія, онкологія і морфологія тварин». Національний університет біоресурсів і природокористування України. Київ, 2021. Дисертацію присвячено вивченню морфофункціональних змін в оці тварин експериментального та спонтанного характеру, а також впливу на активність відновлювальних процесів залежно від способу введення мезенхімальних стовбурових клітин. Наведено результати макроскопічних і клінічних досліджень (тесту Шиммера, офтальмоскопії, біомікроскопії щілинною лампою, флюоресцеїнового тесту Зейделя, тонометрії, сонографії) на 7, 14, 30 добу після початку лікування та гістологічних досліджень після виведення тварин з експерименту. За введення алогенних мезенхімальних стовбурових клітин (за увеїтів, експериментального кератиту, ерозій, виразок) спостерігається активізація та прискорення репаративних процесів, починаючи вже з 7 доби експерименту, після трансплантації алогенних мезенхімальних стовбурових клітин, які вводили різними шляхами, залежно від патологічного процесу. За цих умов відбувається значне відновлення експериментально пошкодженої тканини ока, і вже на 30 добу експерименту мікроструктура ока була досить наближеною до такої в нормі. Доведено, що за клінічних випадків у собак із увеїтами/кератитами, виразками, ерозіями спостерігається значне видужання (відновлення тканин) вже на 30 добу, яке фіксувалося клінічно за допомогою тесту Шиммера, біомікроскопії щілинною лампою, флюоресцеїнового тесту Зейделя, тонометрії, сонографії на 7, 14, 30 добу після початку лікування травм очей.
Dissertation for the degree of candidate of veterinary sciences on specialty 16.00.02 «Рathology, Oncology and Morphology of Animals». National University of life and environmental sciences of Ukraine. Kyiv, 2021. The dissertation is devoted to the study of the nature of morphofunctional changes in the eye of experimental and spontaneous nature, as well as the influence on the activity of regenerative processes depending on the method of introduction of mesenchymal stem cells. The results of macroscopic, clinical studies (Schimmer test, ophthalmoscopy, slit lamp biomicroscopy, fluorescent Seidel test, tonometry, sonography) for 7, 14, 30 days after treatment and histological examination after withdrawal of animals from the experiment. With the introduction of allogeneic mesenchymal stem cells (to eliminate experimental keratitis, erosion, ulcer) is the activation and border repair of relative processes, starting with 7, the experiment is obtained after transplantation of allogeneic mesenchymal stem cells, called different washers. there is a significant recovery of experimentally damaged eye tissue and for 30 days of the experiment the microstructure of the eye should be close to normal. It is proved that in clinical cases in dogs with conditions/keratitis, ulcers, erosions, there is a significant recovery (tissue repair) for 30 days, which was recorded clinically using (Schimmer test, slit lamp biomicroscopy, fluorescein Seidel test, sono on 7, 14, 30 days after the start of treatment of eye injuries. For the first time, the effectiveness of various methods of allogeneic mesenchymal stem cells was tested, namely: introduction into the tenon space, subconjunctival, intravitreal, anterior chamber of the eye, as well as various techniques of amniotic membrane application (layer-by-layer transplantation technique, biological bandage, application shell). With the introduction of allogeneic mesenchymal stem cells into the tenon space and the use of the amniotic membrane at the site of experimental damage to the animal's eye, the regeneration process is more intense than after other methods of allogeneic mesenchymal stem cells. The obtained research results can be used in the scientific field to deepen knowledge about the influence of stem cells on regenerative processes in the eye of animals and in clinical practice for spontaneous manifestations, as one of the alternative methods of treating animals for eye tissue damage, and in educational work to study features. regeneration of eye tissues in animals under the influence of allogeneic mesenchymal stem cells. The influence of allogeneic mesenchymal stem cells on the activity of regenerative processes in the eyes of rabbits and dogs with uveitis/keratitis has been established; the dependence of the effectiveness of allogeneic mesenchymal stem cells on the method of their introduction (tenon space, subconjunctival, intravitreal, anterior chamber of the eye) was tested. A comprehensive approach to the use of surgical techniques of amniotic membrane transplantation (layerbylayer transplantation, biological coating) and the use of amniotic membrane extract in the form of a gel is used. Changes in the eye of rabbits in experimental and spontaneous course in dogs with uveitis/keratitis and indicators (Schimmer test, biomicroscopy with a slit lamp, fluorescein Seidel test, tonometry, sonography) and macroscopic and histological changes in the eye, which allowed to obtain results all stages of reparative regeneration. It was found that the activity of regenerative processes in animals with experimental keratitis / uveitis depends on the method of introduction of mesenimal stem cells. The highest activity of regenerative processes according to the indicators of sonographic research methods, slit light biomicroscopy and tonometry, which were confirmed histologically, are observed for introduction into the anterior chamber of the eye and into the tenon space for anterior uveitis. Slightly lower activity of regenerative processes in the tissues of the anterior chamber of the eye was observed with intravitreal and subconjunctival administration, and the lowest – with traditional treatment. It was found that the most effective way to regenerate damaged superficial layers of the cornea with keratitis in rabbits and dogs is a surgical technique of biological coating and application of homogenized amniotic membrane extract in the form of a gel, as evidenced by complete epithelialization of the corneal surface. for 30 days. It was noted that the regenerative processes were most effective in the group of animals to which allogeneic mesenchymal stem cells were injected directly into the epicenter of the inflammatory process. The traditional method of treatment showed significantly lower results. According to the results of immunological studies in different phases of the inflammatory process in the eye there were no changes in the decrease or increase in immunoglobulin levels relative to physiological parameters before and after the introduction of allogeneic mesenchymal stem cells in eye tissues, which confirms the absence of any allergic reactions. In keratitis in dogs, the effectiveness of the use of amniotic membrane extract in the form of a gel has been proven in comparison with the traditional method, which was significantly more effective and can be used as a main or auxiliary material in the treatment of severe spontaneous eye pathology
Keywords: мезенхімальні стовбурові клітини; око; репаративний процес; клітинний матеріал; амніотична оболонка; увеїт; експериментальний кератит; дегенеративні процеси; mesenchymal stem cells; eye; reparative process; cellular material